The Principles of Religion by Rabban Daniel Ibn al-Ḥaṭṭāb: A 13th century synopsis of Syriac Orthodox belief : Critical edition, translation and commentary - Burke, Simon Luke Robinson, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
"The most important of all things sought." Thus the Syriac Orthodox monk Rabban Daniel Ibn al-Ḥaṭṭāb describes the subject of The Principles of Religion , written in the 13th century, probably in South-East Anatolia. In this treatise, Rabban Daniel Ibn al-Ḥaṭṭāb systematically explained and defended fundamental commitments of Syriac Orthodox theology. This volume provides an introduction, a critical edition of the Arabic text, an English translation, and extensive commentary on the influences on The Principles of Religion , particularly from Syriac sources. This editio princeps offers the reader a new window into the literary culture of the Syriac Orthodox Church during the years of the Syriac Renaissance.